Inhibition of STAT3 acetylation is associated with attenuated renal fibrosis in the obstructed kidney - NI Jun; SHEN Yang; WANG Zhen; SHAO De-cui; LIU Jia; FU Lan-jun; KONG Ya-li; ZHOU Li; XUE Hong; HUANG Yu; ZHANG Wei; YU Chen; et al. (Acta Pharmacologica Sinica, 2016)
Jun NI1, Yang SHEN1, Zhen WANG1, De-cui SHAO1, Jia LIU1, Lan-jun FU2, Ya-li KONG1, Li ZHOU1, Hong XUE1, Yu HUANG3, Wei ZHANG1, Chen YU2, *, Li-min LU1, * 1Department of Physiology and Pathophysiology, Shanghai Medical College, Fudan University, Shanghai 200032, China; 2Department of Nephrology, Tongji Hospital, Tongji University School of Medicine, Shanghai 200065, China; 3School of Biomedical Sciences and Institute of Vascular Medicine, Chinese University of Hong Kong, Hong Kong, China Aim:To explore the relationship between the signal transducer and activator of transcription 3 (STAT3) signaling and renal fibrosis. Methods: Rat renal tubular epithelial NRK-52E cells were treated with angiotensin II (Ang II), nicotinamide (an inhibitor of NAD+-dependent class III protein deacetylases, SIRT1–7), or resveratrol (an activator of SIRT1). Mice underwent unilateral ureteral obstruction (UUO) were used for in vivo studies. Renal interstitial fibrosis was observed with HE and Masson’s trichrome staining. STAT3 acetylation and phosphorylation, fibronectin, collagen I, collagen IV, and α-smooth muscle actin (α-SMA) levels were examined using Western blotting. Results: Nicotinamide (0.625–10 mmol/L) dose-dependently increased STAT3 acetylation on Lys685 and phosphorylation on Tyr705 in NRK-52E cells, accompanied by accumulation of fibronectin and collagen IV. Ang II increased STAT3 phosphorylation on Tyr705 and the expression of fibronectin, collagen IV and α-SMA in the cells. Pretreatment with resveratrol (12.5 μmol/L) blocked Ang II-induced effects in the cells. UUO induced marked STAT3 phosphorylation, fibronectin, collagen IV and α-SMA accumulation, and renal interstitial fibrosis in the obstructed kidneys, which were significantly attenuated by daily administration of resveratrol (100 mg/kg). Conclusion:STAT3 acetylation plays an important role in activation of STAT3 signaling pathway and consequent renal fibrosis. Keywords: chronic kidney disease; renal fibrosis; unilateral ureteral obstruction (UUO); angiotensin II; resveratrol; nicotinamide; STAT3; acetylation; phosphorylation This research was financially supported by the National Natural Science Foundation of China (No 81070577, 81170636) to Li-min LU, (No 81000280) to Hong XUE, (No 81100531) to Wei ZHANG and (No 81070547) to Chen YU. * To whom correspondence should be addressed. E-mail yuchen2001@hotmail.com (Yu CHEN); lulimin@shmu.edu.cn (Li-min LU) Received 2013-12-03 Accepted 2014-04-25